Bombus jonellus Kirby 1802 ... - Ornosa, Concepción; Torres, Félix; Rúa, Pilar De La (Zenodo, 2017)
Bombus jonellus (Kirby, 1802) Palearctic species, that occurs from the Pyrenees and the Cantabrian Range, to the Barents Sea coast, from Iceland in the west to Kamchatka in the east. In Europe, it is considered as Least Concern (Rasmont et al. 2015). The Pyrenean population consists of one unique subspecies: ... : Published as part of Ornosa, Concepción, Torres, Félix & Rúa, Pilar De La, 2017, Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status, pp. 41-77 in Zootaxa 4237 (1) on page 57, DOI: 10.11646/zootaxa.4237.1.3, http://zenodo.org/record/322688 ...